2008
DOI: 10.1093/rheumatology/ken395
|View full text |Cite
|
Sign up to set email alerts
|

Common inflammatory mediators orchestrate pathophysiological processes in rheumatoid arthritis and atherosclerosis

Abstract: RA is characterized by a systemic inflammatory state, in which immune cells and soluble mediators play a crucial role. These inflammatory processes resemble those in other chronic inflammatory diseases, such as atherosclerosis. The chronic systemic inflammation in RA can be considered as an independent risk factor for the development of atherosclerosis, and represents an important field to investigate the reasons of the increase of acute cardiovascular events in RA. In the present review, we focused on several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
110
1
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(124 citation statements)
references
References 280 publications
(266 reference statements)
1
110
1
12
Order By: Relevance
“…There are several similarities between the inflammatory and immune mechanisms of the atherosclerotic process, the major substrate of CVD and CID (2). Hence, it has been suggested that CID may be associated with a high risk for development of atherosclerosis early in the course of the disease, leading to increased incidence of CVD in the long term (3).…”
Section: Introductionmentioning
confidence: 99%
“…There are several similarities between the inflammatory and immune mechanisms of the atherosclerotic process, the major substrate of CVD and CID (2). Hence, it has been suggested that CID may be associated with a high risk for development of atherosclerosis early in the course of the disease, leading to increased incidence of CVD in the long term (3).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, it has become evident that upregulation of inflammation and autoimmune aggression in certain systemic disorders such as systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) may substantially accelerate atherogenesis and increase the risk of vascular events [10][11][12]. Basic and clinical research studies in this *Address correspondence to this author at the Boğaziçi University, Department of Molecular Biology and Genetics, 34342 Bebek/Istanbul, Turkey; Tel: +90(212) 359-77-84; Fax: +90 (212) 287-2468; E-mail: sahru.yuksel@boun.edu.tr field have led to the emergence of a new biomedical discipline, vascular rheumatology [13], which aims to clarify pathophysiology of rheumatic diseases and co-morbidities and to propose recommendations for primary and secondary prevention of vascular events in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that in patients with various infectious and non-infectious diseases, the production of inflammatory cytokine increases [18]. Also, this condition occurs in other chronic situations such as cystic fibrosis [19], Rheumatoid arthritis and atherosclerosis [18], pulmonary fibrosis, chronic osteomyelitis, and allergic asthma [11] [20] [21] [22]. IL-1 plays an important role in pathogenesis and maintenance of CNS diseases, such as multiple sclerosis, Alzheimer and clinical evolution of coronary artery diseases.…”
Section: Discussionmentioning
confidence: 99%